Amanda Berenguer: mixed genres - Kuzminskaitè, Dovilė (Anales de Literatura Hispanoamericana, 2014)
This paper analyses the visual poetry of Uruguayan poet Amanda Berenguer, published in her poetry book Composición del lugar (1976). The aim of the research is to investigate how the poetic text changes applying different artistic techniques and how it influences in the perception of the poem.
Keywords: Amanda Berenguer; visual poetry; Composición del lugar.